A Nationwide Survey on Digestive Reconstruction Following Pharyngolaryngectomy With Total Esophagectomy: A Multicenter Retrospective Study in Japan. Issue 1 (22nd September 2021) - Okamura, Akihiko; Watanabe, Masayuki; Mukoyama, Nobuaki; Ota, Yoshihiro; Shiraishi, Osamu; Shimbashi, Wataru; Baba, Yoshifumi; Matsui, Hidetoshi; Shinomiya, Hirotaka; Sugimura, Keijiro; Morita, Masaru; Sakai, Makoto; et al.
Abstract: Aim: Digestive reconstruction after pharyngolaryngectomy with total esophagectomy (PLTE) remains challenging, with the optimal method remaining unclear. The current study aimed to clarify the short‐term outcomes after PLTE and determine the optimal digestive reconstruction method. Methods: Based on a nationwide survey of 151 patients who underwent PLTE, outcomes of digestive reconstruction methods are described. Results: Among digestive reconstruction methods, a simple gastric tube was most frequently used (37.1%), followed by gastric tube combined with free graft transfer (FGT) (35.1%), gastric tube with microvascular anastomosis (22.5%), and other procedures (5.3%). Intraoperative evaluation of microcirculation (IOEM) was utilized in 29 patients (19.2%). Among the included patients, 66.9% developed any‐grade complications, 41.0% developed severe complications, and 23.8% developed digestive reconstruction‐related complications (DRRCs; leakage or necrosis). Reoperation within 30 days for any complications and DRRCs was required in 13.9% and 8.6% of the patients, respectively. Mortality within 90 days was observed in 4.6%. Among the three major methods, gastric tube combined with FGT promoted the least DRRCs in the gastric tube ( P = .005), although the overall incidence of DRRCs was comparable. The use of IOEM was significantly associated with a reduction of severe DRRCs ( P = .005). Conclusions: Pharyngolaryngectomy with total esophagectomy is a high‐risk surgery significantly associated with the occurrence of postoperative morbidity and mortality. Nonetheless, the addition of FGT can help prevent gastric tip complications, while IOEM can be an effective method for improving outcomes. Abstract : In this nationwide survey on digestive reconstruction following pharyngolaryngectomy with total esophagectomy, reconstruction using a gastric tube with free graft transfer was significantly associated with fewer digestive reconstruction‐related complications (DRRCs) in the gastric tube. However, it did not decrease overall and severe DRRCs. Intraoperative evaluation of microcirculation significantly reduced severe DRRCs.